Electrochemical degradation of phenol by in situ electro-generated and electro-activated hydrogen peroxide using an improved gas diffusion cathode. (20th December 2015) - Luo, Haijian; Li, Chaolin; Wu, Chiqing; Zheng, Wei; Dong, Xiaoqing
Graphical abstract: Highlights: The improved gas diffusion electrode could effectively enhance H2 O2 productivity. Phenol was availably degraded by IGDE without adding any metal catalyst. Effective degradation of phenol in an basic medium broadened the working pH range. Free radical was generated by electro-activated H2 O2 in the IGDE interface. ABSTRACT: Electro-Fenton process represents an attractive and effective technology in destroying hazardous and organic pollutants. However, the low H2 O2 productivity and the narrow working pH range have been limiting its further industrial application. In this study, an improved gas diffusion electrode constructed by carbon black and PTFE was designed to improve H2 O2 productivity. The diaphragm electrolytic device was then used to degrade phenol without adding any catalyst. Results showed that the maximum concentration of H2 O2 was 275.5 mM, which was roughly eight times higher than the value obtained by traditional reference cathode. The effects of the operation parameters, such as current density, supporting electrolyte, pH, air flow rate, and phenol concentration, on phenol removal were systematically optimized. Under the optimum conditions, phenol removal reached almost 100% after 40 min and the mineralization efficiency in terms of TOC exceeded 85% after 120 min. Experiments indicated that the degradation of phenol in the electrochemical process was dominated by radical based mechanisms, which was obtained by the electro-generation and the subsequent electro-activation of H2 O2 at the cathode interface. It is suggested that the electro-activated H2 O2 process with less influence of pH and ferrous is a potential method for the electrochemical degradation process.